Effect of boron addition on the rolling contact fatigue strength of Fe-Ni-Mo-B-C sintered alloys - Shigeki EGASHIRA (The Japan Society of Mechanical Engineers, 2020)
Sintered materials are superior in productivity because of their simple process, but they are not applied to high-load gears because of their insufficient strength. To improve the fatigue strength of sintered materials, the authors have developed liquid-phase sintering which can achieve high-density without using secondary processing. In this study, the effect of boron addition (0-0.4 mass%) on the rolling contact fatigue strength of Fe-Ni-Mo-B-C sintered and carburized material was evaluated. In addition, in order to evaluate only the boron addition effect excluding the influence of density, the sintered density of each specimen was controlled to be the same. In the test range of this study, the rolling contact fatigue limit (pmax)lim of material with an additional quantity of boron of 0.1 mass% showed the highest value exceeding 1700 MPa. This value was not only significantly higher than the (pmax)lim of the boron-free material (1100 MPa), but also an extremely high value comparable to the (pmax)lim of wrought steel (1900 MPa). The reason why the (pmax)lim of a 0.1B roller was remarkably high was investigated from the viewpoints of both pore structure and material structure. As for the pore structure, the pore shape of the boron-free roller was irregular, whereas the pore shape of the 0.1B roller was spherical. As a result of CAE analysis of the orthogonal shear stress inside the roller during the rolling contact fatigue test, it was found that the maximum value of orthogonal shear stress around the pores of the 0.1B roller was about 35 % lower than that of the boron-free roller. This result suggests that cracks are less likely to occur in the 0.1B roller than in the boron-free roller. In other words, it is thought that the pore shape of 0.1B material affects the improvement of rolling contact fatigue strength.